To analyse the semen for various parameters with special reference to lifestyle factors - Aswal, Abhinav; Sharma, Sangeeta; Bansal, Rani; Khare, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Male factor is responsible for infertility in 23% cases. Semen analysis is the cornerstone of infertility evaluation as it provides information on the functional status of seminiferous tubules, epididymis and accessory sex glands. Reports in recent years has shown that incidence of male infertility has increased as a result of various factors such as lifestyle, environmental pollution and stress. Methods: This prospective study was conducted on patients reporting for semen analysis in Department of Pathology, Subharti Medical College. The duration of the study was from October 2014 to September 2016 with a study sample of 196 cases. Semen analysis was done by manual method according to WHO 2010 criteria. Results: According to fertility scoring, out of 196 cases, 51 (26%) were infertile cases. With respect to infertile cases 82.4% were alcoholic, 80.4% tobacco smokers, 25.5% were tobacco chewers. These results were statistically significant. Out of 45 cases of oligozoospermia 37 (82.2%) were alcoholic, 36 (80%) were tobacco smoker and 10 (22.2%) were tobacco chewers. Out of 54 cases of asthenozoosperma 38 (70.4%) were alcoholic, 37 (68.5%) were tobacco smoker and 11 (20.4%) were tobacco chewers. Conclusions: Alcohol consumption, tobacco smoking and tobacco chewing have a significant negative effect on the process of spermatogenesis, ultimately affecting sperm concentration, viability and motility. Hence clinician and fertility counselors need to be more focused to control infertility by modifying the life style factors.